Right (Subjective) to the Criminal Non-Prosecution Agreement and Judicial Control: Reflections in the Light of the Fundamental Rights Theory - Augusto César Leite de Resende (Revista Brasileira de Direito Processual Penal, 2020)
Act N. 13.964/2019, called the “Anti-Crime Package”, regulated the decriminalizing institute of the “Criminal Non-Prosecution Agreement”. With the legislation on the legal benefit in force, arise a great controversy in the national legal scene about the legal nature of the new institute and about the possibility of judicial control of the refusal of the Ministry for Public Affairs to offer it. For this reason, the purpose of this scientific article is to analyze, based on deductive, bibliographic and legislative research, the legal nature of the “Criminal Non-Prosecution Agreement” and on the possibility of judicial control over the refusal of the Ministry for Public Affairs to propose to the investigated such a benefit, in the light of the theory of fundamental rights. To conclude, in the end, that the “Criminal Non-Prosecution Agreement” is the subjective right of the investigated person and that the Judiciary can control the legality of the act of refusing the benefit by the Public Ministry, granting it if the legal requirements are fulfilled.